1999
DOI: 10.1136/bjo.83.12.1376
|View full text |Cite
|
Sign up to set email alerts
|

Role of ocular matrix metalloproteinases in peripheral ulcerative keratitis

Abstract: Aim-Peripheralulcerative keratitis (PUK) is an ocular manifestation of rheumatoid arthritis and other similar systemic diseases. The purpose of this inquiry was to investigate the involvement of matrix metalloproteinases (MMPs) in the induction and/or maintenance of PUK. Methods-Substrate gel electrophoresis was used to characterise the MMP activities secreted by primary cultures of keratocytes derived from normal and perforated pathological corneal specimens, and those present in tears of normal subjects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
2
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 24 publications
1
58
2
5
Order By: Relevance
“…The M r 62,000 species is generally considered to represent the activated form of MMP-2 generated by the loss of an Nterminal peptide [16,17] through the action of membrane-bound MMPs [18,19]. Despite these reports, and in agreement with our previous findings [10,11,20], the transformation of the M r 66,000 species into the M r 62,000 species did not generate activated enzyme capable of hydrolysing denatured [ 3 H]type 1 collagen. Hydrolysis of this substrate was catalyed only by the soluble protein preparations that also contained the M r 43,000 zymographic activity and were generally those that had been maintained in culture medium for periods exceeding 30 days.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The M r 62,000 species is generally considered to represent the activated form of MMP-2 generated by the loss of an Nterminal peptide [16,17] through the action of membrane-bound MMPs [18,19]. Despite these reports, and in agreement with our previous findings [10,11,20], the transformation of the M r 66,000 species into the M r 62,000 species did not generate activated enzyme capable of hydrolysing denatured [ 3 H]type 1 collagen. Hydrolysis of this substrate was catalyed only by the soluble protein preparations that also contained the M r 43,000 zymographic activity and were generally those that had been maintained in culture medium for periods exceeding 30 days.…”
Section: Discussioncontrasting
confidence: 47%
“…In addition to supporting the hypothesis that MMP-2 can become activated in organ cultured corneas, these observations also suggested that the M r 43,000 form of MMP-2 is the catalytically active species present, perhaps because it cannot effectively bind the tissue inhibitors of metalloproteinases 2 and 1 that are co-secreted by keratocytes [9,11,21]. With respect to the activity status of the M r 62,000 form of corneal MMP-2, this has been questioned previously [10,11,20]. However, if it is capable of catalysing peptide bond hydrolysis, it must remain complexed with tissue inhibitors of metalloproteinases, and thus inhibited, in corneal tissue.…”
Section: Discussionmentioning
confidence: 85%
“…The production of matrix metalloproteinases (MMPs) by corneal fibroblasts is responsible in part for the remodeling of collagen fibrils in the corneal stroma. 3,4 The production of tissue inhibitors of MMPs is also a determinant of collagen remodeling associated with corneal disease. 5,6 Proinflammatory cytokines such as interleukin (IL)-1b and IL-6 also contribute to the pathogenesis of inflammatory corneal disease.…”
mentioning
confidence: 99%
“…Such studies show the progression of corneal melting to be influenced by the elaboration of excessive tissue degradative proteases. [6][7] One group of these proteases are the matrix metalloproteinases (MMPs). MMPs are regularly shown to have a role both in infectious and noninfectious causes of corneal tissue destruction.…”
mentioning
confidence: 99%
“…MMPs are regularly shown to have a role both in infectious and noninfectious causes of corneal tissue destruction. [6][7][8] From animal and laboratory studies, a variety of agents or surgical approaches are proposed as potential inhibitors of MMPs. Some of these have been used in human patients.…”
mentioning
confidence: 99%